HADİSLERİN TEÂRUZUNDA SEM’ÂNÎ’NİN Ö. 489/1096 TAKİP ETTİĞİ TERCİH YÖNTEMLERİ - Uzundağ, Mehmet Sait (Fırat University, 2017)
Hadislerin teâruzu problemi, ilk zamanlardan beri hadis alimlerini en çok uğraştıran konulardan biri olmuştur. Hadislerde görülen ihtilaf ve teâruzun tespiti, sebepleri ve çözümü için birçok metod geliştirilmiş, bu konuda özellikle fıkhi mezhepler kendi mezhebinin metodolojik usulüne uygun olarak farklı yaklaşımlar sergilemişlerdir. Sem’ânî, Hanefi mezhebine mensup olup daha sonra Şafii mezhebini tercih eden ve mütekellimîn metodunu iyi işleyen Tefsir, Hadîs, Fıkıh, Fıkıh Usûlü, Kelam, Arap Edebiyatı dallarında iyi bir eğitim alan, birçok alanda eserler ortaya koyan önemli bir usûlcüdür. Sem’ânî “Kavâtiu’l-Edille” adlı usûl kitabında Hadis Usulünün konularından biri olan muhtelifü’l hadis konusunu ele almış bulunmuş özellikle teâruz halindeki hadislerin anlaşılmasında kendi mezhebinin görüşleri doğrultusunda çeşitli tercih yöntemlerini kullanmıştır. Bu makalede Sem’ânî’nin takip ettiği tercih yöntemleri hakkında bilgiler verilmeye çalışılacaktır.

The contradiction problem of the Hadiths has been recognized as one of the most controversial issues by Hadith scholars since the earliest times. Many methods have been developed for the determination, reasoning and solution of the controversy and contradiction in the Hadiths and particularly Fiqhi sects have different approaches in this topic in accordance with the methodology of their own sects. Sem’ânî is an important methodologist who were a member of Hanafi sect, later prefered Shafi’î sect, applied the method of mutakallimin and received a good education in the branches of Tafsir, Hadith, Fiqh, the methodology of Fiqh, Kalam, Arabic Literature as well as had works in several fields. He provided explanations about Mukhtalif al-Hadith, a topic of the methodology of the Hadith in his methodology book, named ‘Kavâti’ al-Adilla’ and he used various methods of preference especially in understanding of contradictory Hadiths in accordance with his sect's ideas. In this article, we will give information about the preference methods, followed by Sem’ânî.
Sem’ânî’s d. 489/1096 Methods Of Preferencing Of In The Case of Conflicting Traditions